Maximum intensity breast diffusion MRI for BI-RADS 4 lesions detected on X-ray mammography. Issue 10 (October 2017) - Bickelhaupt, S.; Paech, D.; Laun, F.B.; Steudle, F.; Kuder, T.A.; Mlynarska, A.; Bach, M.; Lederer, W.; Teiner, S.; Schneider, S.; Ladd, M.E.; Daniel, H.; et al.
Abstract : Aim: To investigate an abbreviated, contrast-agent free diffusion-weighted (DW) breast magnetic resonance imaging (MRI) protocol that provides a single image for the radiologist to read in order to non-invasively examine Breast Imaging-Reporting and Data System (BI-RADS) 4 lesions detected using breast cancer screening X-ray mammography. Materials and methods: This retrospective evaluation within a institutional review board-approved, prospective study included 115 women (mean 57 years, range 50–69 years) with BI-RADS 4 findings on X-ray mammography and indication for biopsy over a period of 15 months. Full diagnostic breast MRI (FDP) was performed prior to biopsy (1.5 T). Maximum intensity breast diffusion (MIBD) images were generated from DW images (b = 1, 500 mm/s 2, 3 mm section thickness) of the breast. MIBD and T2-weighted (T2W) images were read by two radiologists and compared to the diagnostic accuracy of an expert reading of the FDP with histopathology as the reference standard. The acquisition time of MIBD and T2W MRI was about 7 minutes. Results: MIBD MRI provided a diagnostic accuracy of 87.93% (95% confidence interval [CI]: 80.58–93.24%) for R1 and 89.66% (95% CI: 82.63–94.54%) for R2. Expert reading of the FDP revealed a similar accuracy of 86.2% (95% CI: 78.67–91.43%). The positive predictive value (PPV) could be increased from 36.2% (95% CI: 28.02–45.28; X-ray mammography alone) to a mean PPV of 80.89% (R1 79.17%, R2 82.16%) using MIBD MRI. Mean reading time was 30 seconds (25%/75 percentile 24.5–41.25). Conclusions: MIBD MRI might be of supplemental value if added to the work-up of BI-RADS 4 X-ray mammography screening findings. MIBD MRI might help reduce the false-positive rate prior to biopsy for reference lesions at only limited expense of measurement and reading time. Highlights: MIBDI-MRI can help to non-invasively characterize BI-RADS 4 X-ray mammography lesions. MIBDI-MRI only needs limited measurement and reading time. MIBDI-MRI increased the positive predictive value (PPV) from 36.2% to 80.89%. Radiologist mean reading time for MIBDI-MRI was about 30 seconds per patient.